The Influence of Work Environment and Work Stress on Employee Satisfaction at PT Denko Wahana Industries - Oki Rinaldi; Dewi Susita; Agung Wahyu Handaru (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2021)
AbstractThe purpose of this study was to determine a description of the work environment, job stress and job satisfaction of PT Denko Wahana Industri employees, to test and analyze the effect of work environment on job satisfaction of employees of PT Denko Wahana Industri, to test and analyze the effect of job stress on employee job satisfaction. PT Denko Wahana Industri. This study uses the Partial Least Square (PLS) method to analyze data. The research model used in this research is descriptive explanatory. This study was conducted on 154 employees, with a purposive sampling technique. The data collection technique used a survey method, namely distributing questionnaires which were then processed by the SmartPLS 3.3.3 program. The results of PLS show that there is a significant influence on the work environment and job stress on employee job satisfaction.Keywords: work environment, job stress, and job satisfaction, PT Denko Wahana Industri